Four Conditions for Recognition of Traditional Society in the Constitution and State Revenue Income - Adnyani, Ni Ketut Sari; Atmaja, Gede Marhaendra Wija; Sudantra, I Ketut (Universitas Negeri Semarang, 2021)
This article is an interpretation of Article 18B paragraph (2) of the Indonesian constitution: four requirements for recognition of traditional societies. Using sustainable tourism development as a case study, explores the important contribution of genealogical territorial participation and the limits of recognition of the role of the State in providing legal protection and traditional societies as the main coders of legal pluralism. This exploration reveals four different conditions: conditions for survival, dynamic conditions, conditions in accordance with the principle of integration, and regulated by law. The fact that these conditions are so intricately interwoven poses unique challenges for academics and legal practitioners, but also provides a potential blueprint for constitutions and state revenues.